MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN MAHARAH ISTIMA’: STUDI KASUS DI TMI AL-AMIEN PRENDUAN - -, Namlul Wadi; Nur hasaniyah; Abdul Muntaqim Al-Anshory (LPPM IAD Probolinggo, 2025)
Listening comprehension (maharah istima’) is a foundational skill in Arabic language learning, particularly for beginner-level students in Islamic boarding schools. However, traditional teaching methods that rely heavily on textbooks and lectures often fail to engage students or support the development of effective listening skills. This study aims to explore the effectiveness of animated video-based learning media in enhancing students' listening abilities in Grade 1 of the Intensive Program at TMI Al-Amien Prenduan. Using a qualitative descriptive approach with a case study design, data were collected through classroom observations, in-depth interviews, and documentation. The findings reveal that the integration of animated videos significantly improves students’ auditory comprehension, vocabulary acquisition, pronunciation accuracy, and learning motivation. Contextual visuals paired with clear audio narration help students better understand Arabic conversations and imitate appropriate expressions and intonations. Furthermore, students exhibit increased engagement, confidence, and active participation during learning sessions. These results affirm the pedagogical value of animated videos as an innovative and effective medium for developing listening skills in Arabic, particularly within the unique educational environment of pesantren. The study recommends the broader implementation of digital multimedia in Arabic curricula to support more engaging and effective language acquisition. Keywords: Animated Video; Listening Skill; Arabic Language; Learning Media; Islamic Boarding School